PERENCANAAN PEMBANGUNAN KOTA BANJAR PROVINSI JAWA BARAT - Adhi Iman Sulaiman; Djuara P. Lubis; Djoko Susanto; Ninuk Purnaningsih (Jurnal Kawistara, 2016)
Development Planning Deliberation (Musrenbang) is the participatory development process, involvingstakeholders to perform the development communication functions in determining and realizingcommon welfare. This research used descriptive of qualitative method, data collection through literaturereview, direct observation, documentation analysis, and interviews. Research locations were conductedin Banjar, West Java Province by using purposive sampling. Research informants consisted of villagehead, facilitator, bureaucratic regional organization and stakeholders as participants of Musrenbang.The results showed that the implementation of Musrenbang was still less to utilize information mediawhich should be given by government to the public or the community, either conventional media,such as announcement media in the village or by used the media of Information and CommunicationTechnology (ICT), such as access of internet network to provide and maintain website at the villagelevel in order to realize the development program which are informative, participatory, collaborative,transparent and accountable.